2019
DOI: 10.1097/coc.0000000000000597
|View full text |Cite
|
Sign up to set email alerts
|

Practical Heart Sparing Breast Cancer Radiation Therapy Using Continuous Positive Airway Pressure (CPAP) in Resource-Limited Radiation Oncology Clinics

Abstract: Purpose: The purpose of this study was to report experiences of practical heart sparing breast radiation therapy (RT) using continuous positive airway pressure (CPAP) in resource-limited radiation oncology clinics. Patients and Methods: Twelve patients underwent computed tomography-simulations with both free-breathing (FB) and CPAP under the individual maximum tolerable air pressure. For each patient, left-sided breast RT plans (9 with breast only, 3 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Improvement in lung dose and heart dose parameters was demonstrated in these experiences [20,24,27,28], highlighting future opportunities to quantify the dosimetric benefits of CPAP-guided MRgRT. In the case of SBRT treatment of lung tumors, the planned target volumes were decreased by 19% to 24% with administration of CPAP [20,29].…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Improvement in lung dose and heart dose parameters was demonstrated in these experiences [20,24,27,28], highlighting future opportunities to quantify the dosimetric benefits of CPAP-guided MRgRT. In the case of SBRT treatment of lung tumors, the planned target volumes were decreased by 19% to 24% with administration of CPAP [20,29].…”
Section: Discussionmentioning
confidence: 87%
“…A pilot study by Goldstein et al looking at stereotactic body radiation therapy (SBRT) for lung tumors under 8-15 cm H 2 O CPAP showed a relative lung volume increase of 32% compared to standard FB [20]. Two clinical trials of women receiving left-sided breast radiotherapy highlighted that implementing CPAP led to increases of total lung volume by 35% and 60%, achieved with 8-15 cm H 2 O and 20 cm H 2 O, respectively [24,27]. One previous study of SBRT patients showed a lesser degree of 8% lung volume increase [23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations